2001
DOI: 10.1016/s1011-1344(01)00160-9
|View full text |Cite
|
Sign up to set email alerts
|

Provitamins and vitamins D2 and D3 in Cladina spp. over a latitudinal gradient: possible correlation with UV levels

Abstract: Provitamin D 2 , vitamin D 2 2 and vitamin D 3 3 were identified in the thallus of a lichen species, Cladina arbuscula (Wallr.) Hale and W.L. Culb. The identification of vitamin D 3 was supported by: (1) co-chromatography in both reverse and straight phase HPLC (high performance liquid chromatography), (2) ultraviolet absorption spectrum, and (3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Interestingly, Wang et al [28] reported variability in the vitamin D level in lichens ( Cladina spp.) as related to UV exposure at different latitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Wang et al [28] reported variability in the vitamin D level in lichens ( Cladina spp.) as related to UV exposure at different latitudes.…”
Section: Resultsmentioning
confidence: 99%
“…The higher shell weights recorded in both organic groups could have been due to the ingestion of tiny stones from the ground and to a higher synthesis of vitamin D 3 (Bar et al, 1999) as a result of a greater exposure to sunlight. Vitamin D is formed in the skin of animals through the following processes: provitamin D, previtamin D, Vitamin D; the conversion of provitamin D to previtamin D is a photochemical reaction requiring ultraviolet B photons (Wang et al, 2001). Analysing results as percentages (yolk, albumen and shell) differences lowered.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these northerners, even when residing near the sea, preferred land-based sources of protein, rather than seafood (Gillie 2012; McPhee 1992), and even today the diets of most Scandinavians is not centered on seafood (Halldorsson et al 2007). Although VD3 is found in the lichen species, C. arbuscula and C. rangiferina , which represent important winter feeds for reindeer and caribou, whether this dietary source altered VD3 status in humans is unclear (Snellman et al 2009; Wang et al 2001). Alternatively, we hypothesize that evolutionary differences in cutaneous structure and function are more likely to provide an explanation for the observed increase in circulating 25-(OH)D3 levels in northern Europeans.…”
Section: Introductionmentioning
confidence: 99%